The short-term and long-term effects of intranasal mesenchymal stem cell administration to noninflamed mice lung - Tynecka, Marlena; Janucik, Adrian; Niemira, Magdalena; Zbikowski, Arkadiusz; Stocker, Nino; Tarasik, Agnieszka; Starosz, Aleksandra; Grubczak, Kamil; Szalkowska, Anna; Korotko, Urszula; Reszec, Joanna; Kwasniewski, Miroslaw; et al. (Frontiers in Immunology, 2022)
Mesenchymal stem cell (MSC)-based therapies remain a promising approach to treat degenerative and inflammatory diseases. Their beneficial effects were confirmed in numerous experimental models and clinical trials. However, safety issues concerning MSCs' stability and their long-term effects limit their implementation in clinical practice, including treatment of respiratory diseases such as asthma, chronic obstructive pulmonary disease, and COVID-19. Here, we aimed to investigate the safety of intranasal application of human adipose tissue-derived MSCs in a preclinical experimental mice model and elucidate their effects on the lungs. We assessed short-term (two days) and long-term (nine days) effects of MSCs administration on lung morphology, immune responses, epithelial barrier function, and transcriptomic profiles. We observed an increased frequency of IFN- producing T cells and a decrease in occludin and claudin 3 as a long-term effect of MSCs administration. We also found changes in the lung transcriptomic profiles, reflecting redox imbalance and hypoxia signaling pathway. Additionally, we found dysregulation in genes clustered in pattern recognition receptors, macrophage activation, oxidative stress, and phagocytosis. Our results indicate that MSCs undergo apoptosis in the non-inflammatory microenvironment inducing low-grade inflammatory responses aiming at the clearance of MSCs graft.